Investigation of the floristic biodiversity of a meadow of the Republic of Adygea - I. N. Djakova (Новые технологии, 2024)
The relevance of the research: the research was carried out within the framework of a joint project of the Faculty of Agricultural Technologies and the Pharmaceutical Faculty “Physic Garden” for the implementation of the Development Program of Maikop State Technological University for 2023-2032. The goal of the research is to study the species composition of a meadow community, to identify medicinal plant species. The research objectives are to study the vegetation cover of meadows of the flat territory of the Republic of Adygea, collection, office processing, determination of meadow vegetation, analysis of flora - taxonomic, bioecological, biomorphological. The research methods: plant species were identified using the field atlas by A.S. Zernov and the guide by I.S. Kosenko [3, 6]. Life forms are presented using the system by K. Raunkier, taxonomic analysis using the work by A.P. Khokhryakova. The object of research is a phytocenosis of a continental dry meadow. The meadow phytocenosis is represented by herbaceous species adapted to growing together; the flora includes 44 species of higher plants from 16 families, 2 classes, and 1 division. The ratio of plants belonging to the dicotyledonous and monocotyledonous classes is approximately 3:1. The Asteraceae and Rosaceae families predominate in the studied flora from the Magnoliopsida class, and the Poaceae family from the Liliopsida class. In terms of the number of species, the basis of the meadow phytocenosis is made up of perennial grasses. The life form assessment according to Raunkiaer showed the prevalence of hemicryptophytes, according to the hydromorphological structure - the majority of mesophytes. The meadow is in a mature stage, since most of the plants are rhizome. The bulk of the vegetation is meadow, weed-meadow and weed. Such herbs as motherwort five-lobed and common yarrow, which are a source of medicinal plant materials included in the State Pharmacopoeia of the 15th edition grow in the meadow.